Aerobic Exercise Combined With Transcranial Direct Current Stimulation Over the Prefrontal Cortex in Parkinson Disease: Effects on Cortical Activity, Gait, and Cognition - Conceição, Núbia Ribeiro [UNESP] (2021)
Background: Since people with Parkinson disease (PD) rely on limited prefrontal executive resources for the control of gait, interventions targeting the prefrontal cortex (PFC) may help in managing PD-related gait impairments. Transcranial direct current stimulation (tDCS) can be used to modulate PFC excitability and improve prefrontal cognitive functions and gait. Objective: We investigated the effects of adding anodal tDCS applied over the PFC to a session of aerobic exercise on gait, cognition, and PFC activity while walking in people with PD. Methods: A total of 20 people with PD participated in this randomized, double-blinded, sham-controlled crossover study. Participants attended two 30-minute sessions of aerobic exercise (cycling at moderate intensity) combined with different tDCS conditions (active- or sham-tDCS), 1 week apart. The order of sessions was counterbalanced across the sample. Anodal tDCS (2 mA for 20 minutes [active-tDCS] or 10 s [sham-tDCS]) targeted the PFC in the most affected hemisphere. Spatiotemporal gait parameters, cognitive functions, and PFC activity while walking were assessed before and immediately after each session. Results: Compared with the pre-assessment, participants decreased step time variability (effect size: −0.4), shortened simple and choice reaction times (effect sizes: −0.73 and −0.57, respectively), and increased PFC activity in the stimulated hemisphere while walking (effect size: 0.54) only after aerobic exercise + active-tDCS. Conclusion: The addition of anodal tDCS over the PFC to a session of aerobic exercise led to immediate positive effects on gait variability, processing speed, and executive control of walking in people with PD.